Transpor Cd(II) Menggunakan Membran Cair Minyak Jagung Dengan Teknik Membran Cair Fasa Ruah - Refinel; Olly Norita Tetra; Mega Silvia (Jurnal Kimia Unand, 2023)
The transport of Cd(II) has been carried out by means of a bulk phase liquid membrane technique with vegetable oil as an environmentally friendly membrane phase. The transport process consisted of 65 mL of Cd(II) solution as the source phase, 50 mL of corn oil as the membrane phase and 120 mL of EDTA solution as the receiving phase. The experimental technique used a magnetic stirrer at a speed of 200 rpm with an equilibrium time of 15 minutes. The concentration of Cd(II) transported to the source and receiving phase was determined by Atomic Absorption Spectroscopy(AAS) at a wavelength of 228.63 nm. It was found that the optimum conditions for Cd(II) transport were at a concentration of 2.8 ppm with pH 6 as the source phase, EDTA concentration of 0.05 M with pH 4 as the receiving phase, stirring speed of 200 rpm, transport time of 120 minutes and equilibrium time of 15 minutes, the amount of Cd(II) transported to the receiving phase reached 19.37% while the remaining in the source phase was 38.54%.